Usefulness of polymerase chain reaction tests in Chagas disease studies - Bautista-Lopez, Norma; Ndao, Momar (Frontiers in Parasitology, 2024)
The Polymerase Chain Reaction (PCR) test is a highly sensitive, specific, and rapid diagnostic tool for Chagas disease. Chagas disease is caused by the protozoan flagellate Trypanosoma cruzi and is endemic to the Americas. While conventional serological methods are still used in the diagnosis of Chagas disease, they are being gradually replaced by molecular methods like PCR. PCR can detect the parasite's DNA in blood or tissue samples from humans and animals, including asymptomatic infections and animal reservoirs. In a study conducted on a colony of New World monkeys, PCR analysis was found to be superior to conventional screening tools for trypanosome infection, although false negatives can still occur. In clinical studies, PCR has been used to assess the effectiveness of Nifurtimox and Benznidazole in treating acute and chronic Chagas patients. However, the presence of low-grade and intermittent parasitemia in peripheral blood, even in the absence of treatment, renders PCR an unreliable test for evaluating successful treatment. Based on this limiting factor, amongst others, we do not believe that PCR is an appropriate gold standard test for Chagas in clinical and preclinical studies. Other diagnostic methods, such as serological and biomarker tests, should be used in conjunction with PCR techniques for more accurate diagnosis of Chagas.